PERBEDAAN INDEKS BIAS MINYAK GORENG CURAH DENGAN MINYAK GORENG KEMASAN BERMEREK SUNCO - Elisa elisa; Juliana Juliana (Syiah Kuala University, 2015)
The purpose of this research was to determine the difference in the refractive index of bulk cooking oil with Sunco branded bottled cooking oil. The data collection was done by measuring the refractive index of cooking oil using refraction method. Data analysis was performed by finding the average price index of refraction of each type of cooking oil. The results of the study explained that Sunco cooking oil refractive index greater than that of bulk cooking oil so it can be concluded that the branded cooking oil Sunco has the most excellent quality.